PENGARUH PENAMBAHAN PROBIOTIK SEBAGAI PENGGANTI ANTIBIOTIC GROWTH PROMOTER MELALUI AIR MINUM TERHADAP KONVERSI PAKAN DAN ANALISIS USAHA AYAM PEDAGING (Broiler) PENELITIAN EKSPERIMENTAL & ANALISIS USAHA - ANITA DWI ANDRIANI (2019)
The purpose of this study was to know the economic analysis in broilers which used probiotic Lactobacillus casei and Lactobacillus rhamnosus supplementation to alternate Antibiotic Growth Promoter (AGP) to feed conversion and body weight. About 40 broilers chicken day old chick were completely randomized into four treatments with each treatment had ten replications. The treatments were P0, P1, P2 and P3 contained with standard feed, standard feed with 0,01 gram AGP/kg feed, standard feed with 0,025 grams probiotic/liter drinking water and standard feed with 0,05 grams probiotic/liter drinking water. Data analysis was carried out using the Analysis of Variance (ANOVA) method, business analysis was carried out by increasing the number of broiler chickens by as many as 100 using XLSTAT then analyzing descriptively. The results showed that there was a significant difference among the treatments (p<0.05). The highest body weight also at P2 and P3 standard feed with 0,025 and 0,05 grams probiotic/liter drinking water with 2.025 and 2.010 gram, and the lowest body weigh at P0 with 100% standard feed with 1.697. The lowest feed conversion was P2 1,62 and P3 1,63, and the highest feed conversion was P0 2,09. P2 also showed the most profitable economic analysis, which had the best results in Break Event Point and Return Cost Ratio. It could be concluded that could be better to give 0,025 grams probiotic/liter dringking water to get the best body weight and profits in poultry.